Comparing the acute responses between a manual and automated blood flow restriction system - Carter, Daphney M.; Chatlaong, Matthew A.; Miller, William M.; Benton, J. Barnes; Jessee, Matthew B. (Frontiers in Physiology, 2024)
The purpose of this study was to compare the acute responses between manual and automated blood flow restriction (BFR) systems. Methods: 33 individuals completed this study. On visit 1, arterial occlusion pressure (AOP, mm Hg), cardiovascular responses, and discomfort (RPE-D) were measured with each BFR system at rest. On visit 2, unilateral bicep curls were completed [30% one-repetition maximum; 50% arterial occlusion pressure (AOP)] with one system per arm. Muscle thickness (MT, cm) and maximal force (N) were assessed before (Pre), immediately (Post-0), 5min (Post-5), and 10min (Post-10) post-exercise. Exertion (RPE-E) and RPE-D were assessed throughout exercise. AOP and repetitions were compared with Bayesian paired t-tests. Other outcomes were compared with Bayesian RMANOVAs. BF10=likelihood of the best model vs the null. Results presented as mean±SD. Results: Supine cardiovascular responses and RPE-D were similar for manual and automated (all BF10≤0.2). Supine AOP for manual (157±20) was higher than automated (142±17; BF10=44496.0), but similar while standing (manual: 141±17; automated: 141±22; BF10=0.2). MT (time, BF10=6.047e+40) increased Pre (3.9±0.7) to Post-0 (4.4±0.8; BF10=2.969e+28) with Post-0 higher than Post-5 (4.3±0.8) and Post-10 (4.3±0.8; both BF10≥275.2). Force (time, BF10=1.246e +29) decreased Pre (234.5±79.2) to Post-0 (149.8±52.3; BF10=2.720e+22), increased Post-0 to Post-5 (193.3±72.7; BF10=1.744e+13), and Post-5 to Post-10 (194.0±70.6; BF10=0.2) were similar. RPE-E increased over sets. RPE-D was lower for manual than automated. Repetitions per set were higher for manual (Set 1: 37±18; Set 4: 9±5) than automated (Set 1: 30±7; Set 4: 7±3; all BF10≥9.7). Conclusion: Under the same relative pressure, responses are mostly similar between BFR systems, although manual led to lower exercise discomfort and more repetitions.